PENINGKATAN HASIL BELAJAR PENJUMLAHAN PECAHAN BERPENYEBUT TIDAK SAMA DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) DI KELAS IV SD - Ayu, Emilda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Process study of quantifying fraction of have unegual denominator to at class student of IV SD Pertiwi 3 still center to teacher and is not to stir a pag the than problems  reality which close to student. Mean result assessment RPP cycle  67.85%,  cycle  II  82.14%. Mean result  perception  activity learn  cycle  is 71.87 , cycle II 79.68%. Perception Activity cycle student  67.18% cycle  II  82.61%. Mean result learning cycle student 67.68 cycle  II 79.00